When Worse Is Better: Strategic Choice of Vendors with Differentiated Capabilities in a Complex Cocreation Environment - Gupta, Shubham; Roy, Abhishek; Kumar, Subodha; Mudambi, Ram (Management Science, 2023)
The growing complexity of consulting, new product development, and information technology projects has led firms to increasingly adopt the strategy of collaborative value cocreation with their vendors. Although such value cocreation often involves a client firm engaging with more than one vendor, research in this field has primarily focused on single-vendor cocreation, whereas research on multivendor sourcing has rarely considered collaborative value cocreation. We bridge this gap by studying a cocreation environment involving a client, a primary vendor, and a potential secondary vendor. Examining the trade-offs that arise in the strategic interactions among the three firms, we derive novel insights about how these interactions differ from those under one-vendor cocreation, and from those under traditional multivendor sourcing. Specifically, we demonstrate that the client can sometimes be better off by adding a secondary vendor that is less efficient than the primary one; and a more expensive primary vendor can sometimes make the client less inclined to add the secondary vendor. The client’s decision to add the secondary vendor is driven by the value per unit of output rather than purely cost or efficiency parameters. We show that in such collaborative environments, the primary vendor benefits from the addition of a secondary vendor whenever it benefits the client. The conceptual and managerial insights drawn from our research contribute to a better theoretical and practical understanding of strategic decision making by firms in multivendor cocreation environments that are increasingly becoming prevalent. This paper was accepted by Jayashankar Swaminathan, operations management. Supplemental Material: Data and the e-companion are available at https://doi.org/10.1287/mnsc.2022.4490 .